Respuesta :

Reorder the terms: -2.3(-1.2 + x) = -9.66 (-1.2 * -2.3 + x * -2.3) = -9.66 (2.76 + -2.3x) = -9.66 Solving 2.76 + -2.3x = -9.66 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2.76' to each side of the equation. 2.76 + -2.76 + -2.3x = -9.66 + -2.76 Combine like terms: 2.76 + -2.76 = 0.00 0.00 + -2.3x = -9.66 + -2.76 -2.3x = -9.66 + -2.76 Combine like terms: -9.66 + -2.76 = -12.42 -2.3x = -12.42 Divide each side by '-2.3'. x = 5.4 Simplifying x = 5.4

Answer: x = 5.4

Step-by-step explanation: just did the test